ASSESSMENT OF ADEQUACY OF PROTEIN INTAKE IN ENTERAL FEEDING PATIENTS WITH NEUROLOGICAL PROBLEMS - Su May Aung; Wantanee Kriengsinyos; Chanida Pachotikarn; Nipa Rojroongwasinkul (Proceedings of the International Conference on Applied Science and Health, 2017)
Introduction: Enteral tube feeding can provide sole source of nutrients in patients who cannot eat orally. In order to get adequate nutrients, it is essential to choose enteral feeding formula correctly and provide sufficiently. Aims: Therefore this study was carried out to determine the adequacy of protein intake with blenderized tube feeding diet in comparison to traditional tube feeding diet by studying nitrogen balance. Methods: This study was conducted on 25 participants with neurogenic dysphagia who had been admitted to Kwe Ka Baw Hospital at Yangon. The participants were divided into three groups: the first group who received 1800 ml/d of traditional tube feeding diet (Group T, n = 10), the second group was supplied with 1500 ml/d of blenderized tube feeding diet (Group B1, n = 9) and the third group was supplied with 2000 ml/d of blenderized diet (Group B2, n = 6). The nitrogen balance study was done on day 4, day 5 and day 6 of enteral feeding. Results: The mean nitrogen balance of Group T was profoundly negative (-7.3 g/d) and of Group B1 was still negative (-2.6 g/d). The nitrogen balance of Group B2 improved to positive balance (0.6 g/d). In conclusion, the protein intake was inadequate with traditional tube feeding diet and 1500 ml/d of blenderized tube feeding diet. The protein intake was adequate with 2000 ml/d of blenderized tube feeding diet. Conclusion: Based on the result of this study, the blenderized tube feeding diet with 2000 ml/d intake should be recommend to use for enteral feeding patients with underlying neurological problems.